(untitled) (Aldershot, Hants, 2000)
This Handbook contains records for all the major drugs currently used in the treatment of infection. Monographs are provided for 1600 anti-infective agents. For each main entry, the following information is provided: the chemical name and a list of proprietary names and synonyms; the Chemical Abstracts Service (CAS) Registry Number; the European Inventory of Existing Commercial Chemical Substances (EINECS) number; and the Merck Index (12th edition) number. The physical properties of each compound are described and the known biological activity and indicated applications are presented. The structure of each compound is provided, together with a summary of the acute toxicity data associated with it, and the manufacturers and suppliers of the drug are also given. Indexes, including a master index of names and synonyms, are appended.
Keywords: Anti-infective agents,Anti-Infective Agents,Thuốc chống nhiễm trùng,Thuốc chống nhiễm trùng